Effect of the Initial Air Content in Fresh Slurry on the Compressive Strength of Hardened Cemented Paste Backfill - Youzhi Zhang; Deqing Gan; Zhenlin Xue; Xun Chen; Sheng Hu (Advances in Materials Science and Engineering)
Filling mining method can dispose of the tailings into filling slurry, which can be transported to the stope through pipelines to manage the ground pressure and protect the environment. To improve the flowability of filling slurry, additives are used more and more widely. However, some additives can increase the air content in the slurry. The air in the slurry will become pores in the hardened cemented paste backfill (CPB). Therefore, it is necessary to explore the influence of initial air content in fresh slurry on the compressive strength of CPB. In this paper, sodium dodecyl sulfate (SDS) was used to regulate the air content in the fresh slurry. After measuring the initial air content, the slurry was made into test blocks. Then, the uniaxial compressive strength (UCS) of CPB at 28 d age was tested, and the distribution of CPB microscopic pores was observed by scanning electron microscope (SEM). The results show that as the initial air content in fresh slurry increases, the UCS of CPB first increases and then decreases. Before the initial air content in fresh slurry is 6.03%, the CPB pores distribution is relatively uniform. However, after exceeding this value, “discontinuous contact” structures, pore groups, and macropores occur in CPB. Through the CPB microscopic force analysis, the mathematical model describing the effect of initial air content on UCS of CPB should be a combination of logarithmic function and quadratic polynomial. This work can provide a supplement to the theory of CPB strength.